2011
DOI: 10.1038/ki.2011.250
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the antioxidant protein peroxiredoxin 2 contributes to angiotensin II–mediated podocyte apoptosis

Abstract: Podocytes have a significant role in establishing selective permeability of the glomerular filtration barrier. Sustained renin–angiotensin–aldosterone system activation is crucial to the pathogenesis of podocyte injury, but the mechanisms by which angiotensin II modulates podocyte survival due to physiological or injurious stimuli remain unclear. Here, we used proteomic analysis to find new mediators of angiotensin II–induced podocyte injury. Antioxidant protein peroxiredoxin 2 expression was decreased in cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…Podocytes not only respond to AngII through the activation of AT1Rs but are further capable of directly producing intrarenal AngII because of their possession of a local RAS [12,21]. Augmented activation of AngII binding to its receptor AT1R presented in podocytes will induce phenotype shifts, from being dynamically stable to adaptively migratory, causing podocyte depletion and focal segmental glomerulosclerosis [12-14,22]. Under normal physiological conditions, podocytes also play a specific role in the maintenance of intraglomerular RAS balance [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Podocytes not only respond to AngII through the activation of AT1Rs but are further capable of directly producing intrarenal AngII because of their possession of a local RAS [12,21]. Augmented activation of AngII binding to its receptor AT1R presented in podocytes will induce phenotype shifts, from being dynamically stable to adaptively migratory, causing podocyte depletion and focal segmental glomerulosclerosis [12-14,22]. Under normal physiological conditions, podocytes also play a specific role in the maintenance of intraglomerular RAS balance [23].…”
Section: Discussionmentioning
confidence: 99%
“…Podocytes express the AT1Rs, and could thus be injured by enhanced AngII, leading to proteinuria, glomerulosclerosis and even end stage kidney disease [12-14]. Administration of AT1R blockers (ARBs) could prevent the initiation and deterioration of podocyte injury [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that the major cause of Ang II– induced podocyte injury is due to apoptosis in podocytes (9, 10, 16). A reduced podocyte number due to apoptosis induces proteinuria and subsequent glomerulosclerosis (2, 30).…”
Section: Discussionmentioning
confidence: 99%
“…We and others reported that Ang II mediates NADPH-derived superoxide production via Ang II type 1 (AT 1 ) receptor in various types of cells and subsequently induces renal injury (1315). Recent reports revealed that apoptosis contributed to the downregulation of antioxidant protein in podocytes, indicating the involvement of ROS production in podocyte apoptosis (16). …”
Section: Introductionmentioning
confidence: 99%
“…Ang II binds to the receptor AT1 and AT2 to mediate biological functions. Through binding to AT1, Ang II induces vasoconstriction, endothelial dysfunction, atherosclerosis, inflammation, fibrosis and apoptosis [9,10]. On the other hand, renin also directly participates in the development of renal fibrosis through binding to its membrane receptor PRR, thereby triggering intracellular signal transduction and inducing transforming growth factor β1 (TGF-β1) and matrix gene expression [22,23].…”
Section: Intrarenal Ras and The Pathogenesis Of Ckdmentioning
confidence: 99%